(untitled) (Malaysian Journal of Learning and Instruction, 2025)
Purpose - The teaching of thinking skills is not only dependent on pedagogical skills, but also on dispositions. In Malaysia, the teaching of thinking skills is prominent in policy documents, yet weakly embedded in subject teaching. Therefore, the aim of this study was to understand the dispositions of ESL pre-service teachers towards Visible Thinking Routines (VTRs), which are a collection of thinking tools that facilitate different types of thinking. The goal was to identify the salient features of VTRs which shaped the dispositions of ESL pre-service teachers towards teaching thinking. Methodology - Data consisted of 117 written reflective accounts and four focus group discussions involving fifteen pre-service teachers. The participants had experienced VTRs in the following two ways: as learners and as “teachers”. Findings - Participants were largely open and positive towards VTRs. Two main themes reflected this inclination, and they were related to the inherent quality of VTRs which fostered active learning environments, and the systematic framework for teaching thinking skills that VTRs provided. At the same time, there were some less favourable dispositions which were mainly due to finding the “right” routine and implementing VTRs, which resulted in the process being time-consuming. Significance - To shape positive dispositions towards teaching thinking, pre-service teachers should be explicitly taught how to teach thinking and be immersed in a culture of thinking at the teacher education level. This might result in getting pre-service teachers’ acceptance and “buy-in” towards research-based thinking tools such as VTRs, which can be used to integrate thinking skills into subject teaching. Openness to use these tools could later result in “dispositions in action” in these pre-service teachers’ professional careers in the future.